Analisis Pengaruh Tenaga Kerja UKM, Investasi UKM, dan Ekspor UKM Terhadap Pertumbuhan Ekonomi di Indonesia - Denanta Mardian Nugraha; Ignatia Martha Hendrati (UNIVED Press, 2023)
In Indonesia's economic development, SMEs have an important role because it is a sector where many workers are absorbed. The SME sector is a sector that was able to survive the 2 major crises that occurred in Indonesia, namely the Asian financial crisis that took place in 1998 and the global financial crisis in 2008. The purpose and objectives of this research are to analyze whether or not Indonesia's economic growth has been affected by the labor of SMEs, investment SMEs, and exports of SMEs. The multiple linear regression analysis technique was applied in this study so that the results obtained were that Indonesia's economic growth was positively but not significantly affected by the SME labor in 2005-2019. Indonesia's economic growth was negatively and insignificantly affected by SME investment in 2005-2019. Indonesia's economic growth was significantly positively affected by SME exports in 2005-2019.